Nanomagnesium promotes moso bamboo tolerance to cadmium toxicity: insights from photosynthesis phenomics, oxidative metabolism, and cellular adjustments - Shah, Aamir Mehmood; Ulhassan, Zaid; Peng, Yi; Ma, Cong; Du, Xinyu; Iftikhar, Muhammad; Sheteiwy, Mohamed S.; El-Keblawy, Ali; Li, Di; Chen, Qibing; Liu, Shiliang (Frontiers in Plant Science, 2025)
Cadmium (Cd) stress severely hampers plant growth in forest ecosystems. Although magnesium oxide nanoparticles (MgONPs) are known to reduce Cd toxicity in numerous plant species, their detoxification mechanisms in Moso bamboo (Phyllostachys edulis) remain unexplored. The present study investigates how MgONPs mitigate the Cd-induced phytotoxic effects in P. edulis by examining morpho-physiological and cellular oxidative repair mechanisms. Results revealed that MgONPs diminished the oxidative stress by reducing hydrogen peroxide (26/21%), superoxide radical (29/23%), and malondialdehyde (25/20%) contents in leaves/roots under Cd stress. Moreover, MgONPs improved the photosynthetic performance as revealed by higher chlorophyll and gas exchange levels, correlated with better growth and biomass, under Cd stress. Interestingly, MgONPs improved the plant defense by escalating the activities of antioxidant enzymes (ascorbate peroxidase, catalase, and superoxide dismutase) and metabolites (total phenolics, flavonoids, tocopherols) accumulation. Importantly, anatomical analyses verified MgONPs’ role in repairing Cd-induced distortion to stomatal aperture, guard cells integrity and ultrastructural damages. These outcomes demonstrate the MgONPs application greatly enhanced the bamboo tolerance to Cd toxicity by simultaneously regulating the photosynthetic efficiency, multiple antioxidant defense mechanisms, recovering cell damages, and restricting Cd-accumulation. This study provides bamboo-specific mechanistic insights in advancing the understanding of nanoparticles assisted phytoremediation in woody perennials.